Magnetized Rossby waves in mid-latitude ionosphere F-layer - Saliuk, D.A.; Agapitov, O.; Milinevsky, G.P. (Advances in Astronomy and Space Physics, 2012)
We present the results of study of the ionosphere quasi-periodic perturbations on the basis of the analysis of the critical f0F2 frequency variations. The temporal scales of the perturbations are about 7 days and relative amplitude of the f0F2 perturbations are up to 40% of the averaged electron density value. It is assumed from the temporal scale and position that the critical f0F2 frequency variations are caused by Rossby wave-like disturbances with magnetic field influence on the ions. We studied the spatial and temporal scales of the waves at the F-layer altitudes on the basis of the mid-latitude ionosonde network measurements (Millstone Hill, Dyess, and Point Arguello stations data). The generalized Charney-Obukhov equation is proposed to describe the dynamics of the perturbations. We present the numerical model based on the full reduction algorithm for numerical solution of the dynamics equation.